Genome‐wide analysis of single nucleotide variants allows for robust and accurate assessment of clonal derivation in cell lines used to produce biologics. Issue 12 (24th August 2020) - Kuhn, Alexandre; Le Fourn, Valérie; Fisch, Igor; Mermod, Nicolas
Abstract: A clonally derived (or "monoclonal") cell line is a cell population derived from a single progenitor cell. Clonally derived cell lines are required for many biotechnological applications. For instance, recombinant mammalian cells used to produce therapeutic proteins are expected by regulatory authorities to be clonally derived. Assurance of clonal derivation (or "clonality") is usually obtained from the characterization of the procedure used for cell cloning, for instance by assessing the success rate of single‐cell sorting but not by assessing the cell line itself. We have developed a method to assess clonal derivation directly from the genetic makeup of cells. The genomic test of clonality is based on whole‐genome sequencing and statistical analysis of single nucleotide variants. This approach quantifies the clonal fractions present in nonclonal samples and it provides a measure of the probability that a cell line is derived from a single cell. Upon experimental validation of the test, we show that it is highly accurate and that it can robustly detect minor clonal fractions of as little as 1% of the cell population. Moreover, we find that it is applicable to various cell line development protocols. This approach can simplify development protocols and shorten timelines while ensuring clonal derivation with high confidence. Abstract : In many biotechnological applications, the assurance of clonal derivation ("monoclonality") is usually obtained from the characterization of the procedure used for cell cloning. Kuhn et al. have developed a method to assess clonal derivation directly from the cells' genetic material. They show that their "Genomic Test of Clonality" is highly accurate and that it can be integrated into various cell line development protocols. This approach has the potential to simplify development protocols while ensuring clonal derivation with high confidence.